Técnica del cono único y condensación lateral en la obturación de conductos mesiales de primeros molares inferiores - Quispe, Betsy (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of a research presented at the Universidad Nacional del Altiplano, whose objective was to comparatively evaluate the percentage of the area filled with gutta-percha in the apical third of the mesial canals of the first mandibular molars with the single cone and lateral condensation techniques. . Material and Methods: Forty mesial canals were filled for: Group 1 with the single cone technique (N°=20), Group with the lateral condensation technique (N°=20). The pieces were instrumented biomechanically with rotary instrumentation (Navigator System) and with constant irrigation and aspiration, the obturation was proceeded, the cement used in the two techniques was based on calcium hydroxide (Sealapex). After 48 hours of obturation and storage, the samples were sectioned horizontally at 4 and 6mm from the apex with a cutting disc in a low speed micro motor with continuous water irrigation, the thickness of each sample was 2mm. Digital photographs of the sections seen through the stereo microscope were taken to measure the images of the sectioned area of ​​each canal with the Axio Vision software. The total area (mm2) and the sealed area (mm2) were measured. In this way, the percentage of sealed area was found. Results: We proceeded to perform the data analysis and processing. The T-Student test for independent samples was evidenced with a significant value of 5%. There was a significant difference since it was obtained (p = 0.0001) in the percentage of the filled area on average that was reached with the application of the single cone technique, which was 94.39%, while with the lateral condensation technique it reached 92.83%.